Parent-Child Interaction Therapy and young children with Problematic Sexual Behavior: A conceptual overview and treatment considerations. (January 2018) - Shawler, Paul M.; Elizabeth Bard, M.; Taylor, Erin K.; Wilsie, Carisa; Funderburk, Beverly; Silovsky, Jane F.
Abstract: Problematic Sexual Behavior (PSB) can be conceptualized as a distinct subset of externalizing behavior problems. Preschool children with PSB commonly have co-occurring nonsexual behavior problems, including disruptive behavior disorders (DBD). Behavioral parent training is the core component of effective treatments for DBD (Kaminski, Valle, Filene, & Boyle, 2008) and for PSB (St. Amand, Bard, & Silovsky, 2008). Parent-Child Interaction Therapy (PCIT) is an empirically supported evidence-based behavioral parent treatment program for young children ages 2 to 7 with disruptive behavior problems (California Evidence-Based Clearinghouse, 2017; Eyberg & Funderburk, 2011; Funderburk & Eyberg, 2011). However, due to the taboo nature of the topic and the potential impact and harm to other children, unique clinical issues can arise when behaviors are classified as "sexual." Adaptations to PCIT are recommended to address safety, physical boundaries, commonly held myths about the population, and other related issues. Conceptual background of PSB and the fit of behavioral parent training as a core intervention is provided, followed by details regarding augmentations to embed approaches to address PSB within PCIT. Highlights: Young children with PSB often present with clinical levels of disruptive behavior problems. Current treatments have not been found to reduce elevated PSB and elevated behavior problems. PCIT-PSB is proposed for young children with elevated behavior problems and PSB. PCIT-PSB is an augmentation of PCIT that infuses elements of CBT-PSB-P. PCIT-PSB will improve access to care and outcomes for young children with PSB.